Environments of insecurity : domestic violence against migrant wives in the Republic of Korea - Song, Munyi; Resurreccion, Bernadette P.; Doneys, Philippe; Ahmand, Mokbul Morshed; Government of Korea (Pathum Thani, Thailand : Asian Institute of Technology, 2008)
In Korea, the number of migrant women who immigrate to Korea by getting married to Korean men in search of new economic opportunities has increased since 1990s. Unlike migrant wives{u2019} expectations, however, their married lives in Korea entail potential problems, e.g. cultural and racial discrimination, domestic abuse, etc. There appear many cases regarding migrant wives{u2019} suicides or homicide s caused by domestic violence on the newspapers or TV news these days. The purpose of the study is to bring this issue int o the public sphere and to narrow the gap in understanding of intercultural and interracial d ifferences between Korean people and migrant wives. In order to attain its objectives, t he study has explored what the environments of insecurity are which may make migra nt wives vulnerable to domestic violence by examining power relations or power ineq uality shaped by intercultural and interracial differences. Through in-depth interview s with twelve migrant wives from Thailand, the Philippines, and China, four Korean h usbands, and key informants such as directors of NGOs, counselors, etc., the study disc overed that there were disparities in power relations between couples in the process of m arriage and in their married lives as well. It was found through the study that the migrant wiv es{u2019} families in Korea occupy the lowest socio-economic status. The low socio-economical sta tus of migrant wives is determined by that of their husbands and sometimes it is much mor e undervalued by family members and society rather than respected as a full member of t hat society. Migrant wives{u2019} insufficient language ability, lack of understanding in cultural differences among couples, Korean family systems based on patriarchal perspective, th e myth of pure-blood nationalism, and social prejudices in Korean society are elements co ntributing to environments of insecurity which place migrant wives in the situations of dome stic violence. Particularly, migrant wives{u2019} uncertain legal status endows Korean husband s with the right of control over women{u2019}s lives while asking migrant wives to be subj ected to following their husbands. The study mainly argued in its conclusion that Kore an husbands who have joined in violence against their wives are not cognizant enou gh to realize that their migrant wives{u2019} unhappy married lives are a result of their own pro blems. Korean husbands must be open- minded to understand their wives{u2019} situations and th us should stand next to their wives as protectors or supporters and life partners, not as domestic violence perpetrators.
A thesis submitted in partial fulfillment of the re quirements for the degree of Master of Science in Gender and Development Studies, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2008
Keywords: Family violence -- Korea -- Cross-cultural studies; Intercountry marriage -- Korea; Foreign spouses -- Korea